Uma nova abordagem para resolver deficiência de posto, desalinhamento de pico e interferências na análise de aminas biogênicas em peixes usando HPLC-DAD - Pinto Segundo Neto, José Licarion (2018)
Biogenic amines (BAs) are used as food spoilage marker and can cause damage to the body at high concentrations levels. BAs are produced by the action of microorganisms through the enzymatic decarboxylation of natural amino acids. There are several BAs, however only histamine is monitored by a monitoring agency as ESFA (European Food Safety Authority) and FAO/WHO (Food and Agriculture Organization of the United Nations/World Health Organization). Some drawbacks are present in the BAs analyzes. The high electron transition energy requires a derivatization step prior to the HPLC-DAD (high-performance liquid chromatography – diode array detector) analysis. The most common derivation is the one using dansyl chloride. However, this is a non-selective reaction that occurs with any primary or secondary amine, leading to interferers with highly correlated profiles, and resulting in rank deficiency. In addition to rank deficiency, the data present trilinearity break due to time misalignment frequently present in chromatographic data. The most common way of solving rank deficiency is by using a more selective detector, however, this approach increases the cost of analysis and the complexity of data processing, besides not always this selective detector exists. The proposed methodology uses of a four minutes’ isocratic elution, which raises the analytical frequency and is in agreement with the principles of the green analytical chemistry by reducing the solvent consumption. Quantification limits were between 0.08 and 0.15 mg kg-1 for synthetic samples and between 0.04 and 0.17 mg kg-1 for fish samples were obtained with the developed approach, which are way below the maximum limit of 50 mg kg-1 established by FAO/WHO and by the EFSA for histamine in fish. Accuracy results was obtained in the prediction of the sixteen synthetic samples with REP (root error of prediction) varying between 4.0 and 8.0%. BAs were initially identified is fresh fish samples at low concentration levels, however the increase of this concentration can be observed when a kinetic study of degradation of the four samples conditioned at 4 ° C for thirteen days was performed. In this work, the efficiency of the peak alignment with the coshift on restoring the trilinearity of the HPLC-DAD data was shown. So, it was then possible to achieve the secondorder advantage using the MCR-ALS (Multivariate curve resolution - alternating least squares) augmented in the spectral mode. So far there was no proposal to achieve the second-order advantage in data with these characteristics without the previously separation of the constituents that cause rank deficiency or the use of another more selective detector.